Keberlanjutan Pengelolaan Wisata Bahari di Pulau Pari, Kabupaten Kepulauan Seribu - Neksidin; Achmad Fahrudin; Majariana Krisanti (Jurnal Ilmu Pertanian Indonesia, 2021)
Pari Island has considerable natural resource potential, so that it has the potential to have socio-economic impacts on the local community if managed properly. The current management of Pari Island is indeed focused on the management of marine tourism, and this activity has been going on for a long time and has had a very significant impact on the economic sector in Pari Island. On the other hand, marine tourism activities in Pari Island are feared to have an impact on the ecological sector, so that to achieve sustainable management, good supervision and control is needed so that its potential is maintained. The purpose of this research is to see the status of socio-economic and ecological sustainability as a result of the development of marine tourism in Pari Island. The data were collected through in-depth interviews with the people of Pari Island, apart from that the data were also obtained from primary and secondary data related to socio-ecology. To assess the level of sustainability in each dimension, a Multidimensional Scaling (MDS) analysis was carried out, in order to obtain two dimensions that had a value below 75%, namely the institutional dimension which had a value of 27.3% (bad), and the infrastructure dimension which had a value. 73.3% (Enough). Meanwhile, the other 3 dimensions, such as the ecological, economic, and social dimensions, show that the value is in the continuous category, namely> 75% so that it is very supportive of the sustainability of marine tourism business management. Keywords: impact of marine tourism development, marine tourism, Pari Island, sustainable management